Xenophobic Rhetoric and Its Political Effects on Immigrants and Their Co‐Ethnics. Issue 3 (30th December 2014) - Pérez, Efrén O.
<x xml:space="preserve">Abstract</x> Though political scientists generally understand the origins of native‐born reactions to foreigners, less is known about how anti‐immigrant contexts trigger a political response within immigrant groups. I address this question by studying the connection between xenophobic rhetoric and Latino politics. I claim that xenophobic rhetoric raises the salience of ethnic identity and impugns its worth. This identity threat leads high‐identifying group members to engage in political efforts that assert their group's positive value, whereas low identifiers shun political opportunities to bolster their group's devaluation. I test these claims with an experiment embedded in a nationally representative opinion survey of Latino adults. In light of xenophobic rhetoric, I find that relative to low identifiers, high‐identifying Latinos become less politically trusting, more ethnocentric, and increasingly supportive of policies that emphasize ingroup pride. These results clarify xenophobic rhetoric's role in amplifying the influence of ethnic identity on immigrant politics.